CBS News/New York Times Election Surveys, 1976 ([Verlag nicht ermittelbar], 1984)
CBS News and The New York Times were partners in a series of election surveys covering the 1976 United States presidential election campaign. The surveys were intended to provide another dimension to the political reporting of the two organizations. The surveys, using extensive coverage early in the primary campaign, were designed to monitor the public's changing perception of the candidates, the issues, and the candidates' positions vis-a-vis the issues. Parts 1-9 contain separate nationwide surveys conducted by telephone, with approximately 1,500 randomly selected adults. Five surveys were conducted monthly from February through June, and four more between early September and the general election -- one in September and one following each presidential debate. A final survey was conducted two days after the general election. Respondents were asked for their preferred presidential candidate, their ratings of the candidates' qualifications and positions, and their opinions on a variety of political issues. Part 10, the Election Day Survey, contains a national sample of voters who were interviewed at the polls. Respondents were asked to fill out a questionnaire that asked the name of the presidential candidate for whom they had just voted, and other questions about their political preferences. Part 11 contains data for respondents who were first interviewed in Part 9, Debate Three Survey, and recontacted and reinterviewed for the Post-Election Survey. Data include respondents' voting history, their evaluation of the nominees' positions on various political issues, and their opinions on current political and social issues. Parts 12-26 contain surveys conducted in 12 states on the day of the primary at the polling place, among a random sample of people who had just voted in either the Democratic or Republican presidential primary election. These surveys were conducted in the following primary states: California, Florida, Illinois, Indiana, Massachusetts, Michigan, New Hampshire, New York, Ohio, Pennsylvania, and Wisconsin. There are separate files for the Democratic and Republican primaries in Michigan, Ohio, Indiana, and California, making a total of fifteen primary day "exit" surveys. Respondents were asked whom they voted for and why, the issues that were important in making their choice, and their voting history. Demographic information on respondents in all surveys may include sex, race, age, religion, education, occupation, and labor union affiliation. These files were processed by the Roper Center under a cooperative arrangement with ICPSR. Most of these data were collected by CBS News and The New York Times. The Election Day Survey was conducted solely by CBS News. Parts 1-11 were made available to the ICPSR by CBS News.